Associations between long-term air pollution exposure and the incidence of cardiovascular diseases among American older adults. (December 2022) - Jin, Tingfan; Di, Qian; Réquia, Weeberb J.; Danesh Yazdi, Mahdieh; Castro, Edgar; Ma, Tszshan; Wang, Yifan; Zhang, Haisu; Shi, Liuhua; Schwartz, Joel
Graphical abstract: Highlights: A nationwide Medicare cohort study was conducted across the contiguous U.S. Associations were examined using co-pollutant models and at low pollution levels. Potential effect modifications by race/ethnicity and comorbidities were assessed. Air pollution is found associated with incidence of CVD even at low concentration. People who identify as Black or have diabetes are more susceptible to air pollution. Abstract: Background & aim: Numerous studies have linked air pollution with cardiovascular diseases. Fewer studies examined the associations at low concentration levels or assessed potential modifiers. Some investigations only examined hospitalizations, which can miss incident cases. This study aims to address these gaps through a nationwide cohort study of Medicare enrollees. Methods: Our study cohort comprise all Medicare enrollees (≥65 years old) continuously enrolled in the fee-for-service program and both Medicare part A and B across the contiguous U.S. from 2000 to 2016. We examined the associations of population-weighted ZIP code-level annual average PM2.5, NO2, and warm-season O3 (May-October), with the first diagnoses of atrial fibrillation (AF), congestive heart failure (CHF), and stroke. We fit multi-pollutant Cox proportional hazards models adjusted for individual demographic characteristics and area-level covariates. We further examined these associations at low pollutant concentration levels and the potential effect modifications by race/ethnicity and comorbidities (diabetes, hypertension, hyperlipidemia). Results: Elevated PM2.5 and NO2 levels were associated with increased incidence of AF, CHF, and stroke. For each 1 μg/m 3 increase in annual PM2.5, hazard ratios (HRs) were 1.0059 (95%CI: 1.0054-1.0064), 1.0260 (95%CI: 1.0256-1.0264), and 1.0279 (95%CI: 1.0274-1.0284), respectively. For each1 ppb increase in annual NO2, HRs are 1.0057 (95%CI: 1.0056-1.0059), 1.0112 (95%CI: 1.0110-1.0113), and 1.0095 (95%CI: 1.0093-1.0096), respectively. For warm-season O3, each 1 ppb increase was associated with increased incidence of CHF (HR=1.0035, 95%CI: 1.0033–1.0037) and stroke (HR=1.0026, 95%CI: 1.0023–1.0028). Larger magnitudes of HRs were observed when restricted to pollutants levels lower than NAAQS standards. Generally higher risks were observed for Black people and diabetics. Conclusions: Long-term exposure to PM2.5, NO2, and warm-season O3 were associated with increased incidence of cardiovascular diseases, even at low pollutant concentration levels. Black people and people with diabetes were found to be vulnerable populations.